2008
DOI: 10.1007/s12098-008-0111-9
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal nocturnal hemoglobinuria in childhood and adolescence-a retrospective analysis of 18 cases

Abstract: PNH is an uncommon disease in children and should be included in the differential diagnosis of children presenting with cytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
19
2
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 23 publications
7
19
2
5
Order By: Relevance
“…Both sexes can be affected, though our series revealed a slight male preponderance of PNH. Though usually described as hemolytic anemia, PNH-associated cytopenias were common as 85.5% of patients presented thrombocytopenia, neutropenia, or both in our study, which is similar to the results of previous reports [13,17,18,21,22] .…”
Section: Discussionsupporting
confidence: 92%
“…Both sexes can be affected, though our series revealed a slight male preponderance of PNH. Though usually described as hemolytic anemia, PNH-associated cytopenias were common as 85.5% of patients presented thrombocytopenia, neutropenia, or both in our study, which is similar to the results of previous reports [13,17,18,21,22] .…”
Section: Discussionsupporting
confidence: 92%
“…PNH is a rare acquired disorder of hematopoietic stem cells, which mainly presents as a disease of adults and, to a less extent, of childhood and adolescence [3,[21][22][23]. Our report showed that the median age of PNH patients at diagnosis was 32 years, which was similar to some reports [2,7], but younger than others [1,6].…”
Section: Discussionsupporting
confidence: 87%
“…Thrombotic complications in PNH patients can arise in hepatic, cerebral, and deep limb veins [1,24,25]. The development of thrombosis was common in Caucasian but rare in Asian patients with PNH [8][9][10]21]. Our study documented crude incidence of thrombotic events as 3.5%, which was significantly lower than previous reports [2,7], but still remained to be a grave prognostic feature of PNH.…”
Section: Discussionmentioning
confidence: 45%
“…1,[5][6][7]15,16 Our data confirm that thrombosis (TE and MAVE) is an important complication of PNH not only in adults (2.26 per 100 person-years), but also in children (1.23 per 100 personyears). However, myelodysplastic syndrome or myelodysplastic features previously reported in two smaller series 5,7 were not confirmed in our registry cohort.…”
Section: Letters To the Editorsupporting
confidence: 76%